Insight Review on Management of Nephrolithiasis Using Medicinal Plants - Nidhi Sharma, Manu Sharma, Rupa Mazumder, Vaishali Goel, Nitin Kumar, Neeru (South Eastern European Journal of Public Health, 2025)
Background: Urolithiasis or kidney stone is the oldest and most widespread painful urological disorder. Lithiasis refers to the existence of a stone that has emerged in the kidney or any part of the urinary tract. Several conventional approaches for the management of nephrolithiasis or renal calculi such as hemorrhage, infection, urethral perforation, nausea and vomiting are associated with various side effects, which cannot be ignored. Literature has reported multiple medicinal plants and their active components useful in management of urolithiasis with higher safety index compared to conventional approaches. Objectives: In this review article, the nephrolithiasis or urolithiasis properties of herbal medicinal plants in the management of kidney stone highlighted. Conclusion: In consideration of this, current review has summarized the general and comprehensive updated overview of nephrolithiasis activity of medicinal plants. Science direct, Pub Med, Google and Scopus database have been searched for conclusively relevant compositions on herbs and herbal plant based renal calculi studies. The outcomes were screened through analysis of previous abstracts published review and research articles.